The Outcome of Authentic Material-Based Teaching in a Speaking Class - Harsya Danang Pradana; Ouda Eda Tena (Universitas Bengkulu, 2021)
This study was conducted to analyze the language outcome variety of authentic material-based speaking classes of a private university in Yogyakarta. The acceptance of World Englishes variants in the world has led to several changes in English language education, one of them being the focus on native-like accents that has previously been the focus of English language classes. Authentic material, teaching materials created by native speakers of a language, is one way that has been proven to be effective for teaching. However, instead of checking its effectivity, this study researches the language variant of the students. To that end, the researcher interviewed five teachers of speaking classes from a private university in Yogyakarta. The results of the research show that despite all classes using authentic material as a method of instruction, the language variation of the students vary. Some students attained native-like speaking proficiency, while others speak in the Indonesian variety of World Englishes. The future direction of any subsequent research to succeed this one is to find out how this phenomenon could happen.